PP296 Patient Involvement In An Assessment Of The Management Of Sudden Onset Severe Headache Presenting To The Emergency Department. (December 2021) - Wade, Ros; Walton, Matthew; Harden, Melissa; Hodgson, Robert; Eastwood, Alison; Storey, James; Hassan, Taj; Randall, Marc; Hassan, Abu; Williams, John
Abstract : Introduction: Sudden onset severe headache is usually caused by a primary headache disorder but may be secondary to a more serious problem, such as subarachnoid hemorrhage (SAH). Very few patients who present to hospital with headache have suffered a SAH, but early identification is important to improve patient outcomes. A systematic review was undertaken to assess the clinical effectiveness of different care pathways for the management of headache, suspicious for SAH, in the Emergency Department. Capturing the perspective of patients was an important part of the research. Methods: The project team included a patient collaborator with experience of presenting to the Emergency Department with sudden onset severe headache. Three additional patients were recruited to our advisory group. The patient's perspective was collected at various points through the project including at team meetings, during protocol development and when interpreting the results of the systematic review and drawing conclusions. Results: Patients were reassured by the very high diagnostic accuracy of computed tomography (CT) for detecting SAH. Patients and clinicians emphasized the importance of shared decision making about whether to undergo additional tests to rule out SAH, after a negative CT result. When lumbar puncture was necessary, patients expressed a preference to have it on an ambulatory basis; further research on the safety and acceptability of ambulatory lumbar puncture was recommended. Conclusions: Patient input at the protocol development stage helped researchers understand the patient experience and highlighted important outcomes for assessment. Patient involvement added context to the review findings and highlighted the preferences of patients regarding the management of headache.